The Effect of Replacing Peat with Sugarcane Bagasse on the Growth of Cut Flowers and Bulbs of Lily - Guangfen Cui; Wenwen Du; Qing Duan; Xiang Li; Lan Ma; Jihua Wang (Horticulturae)
In order to evaluate the feasibility of using sugarcane bagasse (SCB) as a substitute for peat in lily cultivation, this study examines the effects of replacing different amounts of peat (0%, 25%, 50%, 75%, and 100%) with SCB on the physical and chemical properties of the substrate. The impact on the growth of cut flower and bulbs of the oriental lily variety ‘Siberia’ was investigated. The results show that the pH value, organic matter content, and reducing sugar content of the substrate were significantly increased (p < 0.05) when peat was replaced with SCB. Moreover, the bulk density, permeability porosity, water-holding porosity, and EC value, as well as the contents of hydrolyzed nitrogen, available phosphorus, available potassium, exchangeable calcium, and exchangeable magnesium were significantly decreased (p < 0.05). The bulk density (0.15–0.17 g·cm3), total porosity (64.2–69.6%), and water-holding porosity (41.0–48.4%) of the mixed media were in a suitable range. The addition of SCB led to shorter plant height, a thinner stalk, and a smaller leaf and flower diameter. The contents of total chlorophyll, chlorophyll a and b in leaves, as well as the activities of sucrose synthetase (SS) and sucrose phosphate synthetase (SPS) decreased with the increase in SCB in the substrates at different growth stages of lily cut flowers. The correlation analysis showed that, except for bulb height, other quality traits of cut flowers and bulbs were significantly negatively correlated with the pH, organic matter, and reducing sugar content of substrates. Plant height, stem diameter, leaf number, leaf length and width, flower diameter of cut flowers, as well as the fresh weight, starch content, the activities of SS and SPS of bulbs were significantly positively correlated with the bulk density, total porosity, water-holding porosity, and hydrolyzed N content of substrates (p < 0.05). The load factors of the principal components indicated that the diameter of stem and flower, leaf number, the content of chlorophyll a and b, and total chlorophyll of cut flowers and SPS activity in bulbs could be used as the core indicators for evaluating the suitability of lily cultivation substrate. In conclusion, when the proportion of peat replaced with SCB was lower than 50%, the quality of cut flowers and bulbs was the same as that found with whole peat. Thus, SCB has broad application prospects in the soilless cultivation of lily plants.